Socialization of Technology Ethics in the Context of Social Media Use - Nur'arif, Imaniah Khairina; Ariyandi, Utari; Hanifah, Najwa Nur; Raniah, Hana Sausan; Olivia, Raisa (Jurnal Karya Abdi Masyarakat, 2025)
The ethical use of technology refers to the moral guidelines governing how we utilize technology, including the internet, social media, and other digital devices. At Junior High School (SMP in Bahasa) Ash-Sholihin, many students lack a clear understanding of proper technological ethics, particularly in social media usage. This community service initiative aims to educate students on ethical technology practices in social media. The method employed involves socialization that emphasizes the importance of applying ethical principles in social media use. Activities include material presentations, case studies, and interactive Q&A sessions to enhance students' ethical skills in social media engagement. The target audience for this initiative is the 8th-grade students of SMP Ash-Sholihin. Post-test results indicate that the majority of participants found the material presentation clear, the socialization engaging, and the overall experience beneficial. Thus, it can be concluded that the socialization was successfully understood and positively impacted the target group, namely the 8th-grade students of SMP Ash-Sholihin.